The Immunomodulator 1-Methyltryptophan Drives Tryptophan Catabolism Toward the Kynurenic Acid Branch - Wirthgen, Elisa; Leonard, Anne K.; Scharf, Christian; Domanska, Grazyna (Frontiers in Immunology, 2020)
Background: Animal model studies revealed that the application of 1-methyltryptophan (1-MT), a tryptophan (TRP) analog, surprisingly increased plasma levels of the TRP metabolite kynurenic acid (KYNA). Under inflammatory conditions, KYNA has been shown to mediate various immunomodulatory effects. Therefore, the present study aims to confirm and clarify the effects of 1-MT on TRP metabolism in mice as well as in humans. Methods: Splenocytes from Balb/C or indoleamine 2,3-dioxygenase knockout (IDO1−/−) mice or whole human blood were stimulated with 1-MT for 6, 24, or 36 h. C57BL/6 mice received 1-MT in drinking water for five days. Cell-free supernatants and plasma were analyzed for TRP and its metabolites by tandem mass spectrometry (MS/MS). Results: 1-MT treatment induced an increase in TRP and its metabolite, KYNA in Balb/C, IDO−/− mice, and in human blood. Concurrently, the intermediate metabolite kynurenine (KYN), as well as the KYN/TRP ratio, were reduced after 1-MT treatment. The effects of 1-MT on TRP metabolites were similar after the in vivo application of 1-MT to C57BL/6 mice. Conclusions: The data indicate that 1-MT induced an increase of KYNA ex vivo and in vivo confirming previously described results. Furthermore, the results of IDO−/− mice indicate that this effect seems not to be mediated by IDO1. Due to the proven immunomodulatory properties of KYNA, a shift towards this branch of the kynurenine pathway (KP) may be one potential mode of action by 1-MT and should be considered for further applications.